P0567ACUTE KIDNEY INJURY IN OBSTRUCTIVE UROPATHY; EPIDEMIOLOGY, RENAL OUTCOME AND MORTALITY. (6th June 2020) - Sun, Bong Gyun; Min, Hyeon-jin; Son, Young-Bin; Choi, Eunho; Yang, Jihyun; Oh, Se Won; Kim, Myung-gyu; Jo, Sang-Kyung; Cho, Won-Yong
Abstract: Background and Aims: Urinary tract obstruction (UTO) is a common clinical problem leading to acute or chronic renal impairment. Unlike pediatric population in which congenital anomalies of urinary tract account for a majority of UTO and contribute to end stage renal disease (ESRD), etiologies, clinical manifestation and outcome in adult UTO remain uncertain due to lack of large epidemiological data. Method: We performed a multi-center, retrospective study analyzing 1, 711 patients who underwent percutaneous nephrostomy (PCN) from 2001 to 2015. Results: The most common cause of UTO was malignancies (55.6%) followed by urolithiasis (28.5%) and others. Metastatic colorectal cancer were the most common type of malignancies. Patients with UTO caused by malignancies were significantly older, had more advanced stage acute kidney injury (AKI) and higher mortality rate, while those with urolithiasis had higher prevalence of hypertension, diabetes, cardio-cerebro-vascular diseases. Eighty two percentage of patients developed AKI and 15.2% of patients needed a temporary dialysis. Older age, malignancy associated UTO and high uric acid level were independently associated with AKI. Among patients with AKI, 38.2% patients showed a renal functional recovery defined as eGFR ≥60ml/min/1.73m2 on day 7 after PCN. Multivariate analysis showed that older age and lower hemoglobin level were independent factors predicting a nonrecovery of renal function. During the median follow up period of ∼∼months, overall mortality rate was 33.9% with the highest rate was found in malignancy associated UTO (51.9%), followed by other causes (15.9%) and urolithiasis (8.8%). Malignancy associated UTO (OR 4.754, 95% CI 3.151-7.174, p<0.001), lower albumin level (OR 0.731, 95% CI 0.568-0.942, p<0.001) and stage 3 AKI (OR 2.529, 95% CI 1.332-4.803, p=0.005) were found to be independently associated with mortality. However, the impact of AKI on overall mortality was more prominent in non-malignancy associated UTO with stepwise increase of mortality as KDIGO stage increased. Conclusion: In conclusion, malignancy is the most common cause of upper UTO in adults and AKI is frequently associated. Short term renal recovery after PCN was observed only in 38.2% patients and older age, lower hemoglobin level were associated with nonrecovery of renal function. Malignancy associated UTO showed the highest mortality rate compared to urolithiasis or other causes and stage 3 AKI as well as lower hemoglobin and lower albumin level were found to be independent predictors of mortality in UTO.